Factors influencing people's participation in watershed management programs in Iran - Bagherian, Reza; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ahmad, Shamsuddin (Universiti Putra Malaysia, 2009)
The degree of popular participation in development programs is a major determinant of success or failure, but the factors which make participation efforts successful still remained a mystery. This study was designed to discover this mystery determine the factors that influence local people’s participation in Watershed Management Programs by using the social exchange framework. The data for this study were gathered from 200 respondents through personal interviews during August and September of 2008. The findings of study showed that level of participation in WMP was moderate; however people preferred more involvement in social rather than economical and environmental activities. Correlation analysis showed that six factors: 1) satisfaction of prior programs, 2) attitude toward WMP, 3) knowledge of WMP, 4) alternative income, 5) total income, and 6) expectations of WMP have positive and significant relationship with level of participation in WMP. However, regression analysis discovered that among them five factors provided the best prediction for the level of people’s participation in WMP and explained 45 % of the variation. These five variables were; level of people’s satisfaction of prior programs, their attitude toward WMP, people’s knowledge of WMP, their alternative income, and level of their expectations met of WMP. The result of this study provided a number of theoretical and practical implications and recommendations to increase the level of participation in WMP.